Efficacy of Modified Toggle Splint with Nylon Suture for ‎‎Stabilization of Coxofemoral ‎Luxation in Dogs - Q AL-Samarrai, Mina; A AL-Timmemi, Hameed (The Iraqi Journal of Veterinary Medicine, 2023)
Coxofemoral luxation is a common orthopedic lesion in dogs. This study aimed to evaluate ‎the effectiveness of a modified toggle splint with nylon suture as a prosthetic teres ligament ‎for reducing and fixing coxofemoral luxation in dogs. Five adult mongrel dogs weighing ‎‎15±2 kg were used in this experimental study. The toggle splint was fabricated from a ‎Steinmann pin (1cm length, 2mm diameter) by drilling 0.5 mm hole in the center. ‎Stabilization of coxofemoral joint was performed by a modified Toggle splint technique. A ‎tunnel, from the major trochanter through the fovea capitis to the acetabulum, was ‎performed in which the toggle splint was passed through, and nylon suture was used for ‎fixation. Dogs were scored for lameness severity at 0-, 14-and 42-day post-operation using a ‎numerical rating scale (NRS) with 5 levels, and reductions were assessed radiographically ‎at three-time points the day of operation, day 28th, and day 42nd. The results showed that the ‎treatment splint was effective in achieving good reduction and fixation in four out of five ‎‎(80%) dogs at all time points. Reluxation was observed only in one dog (20%) up to week 6 ‎post-operation. The mean lameness score on day 14 (2.0±0.87) and 42 (0.60±0.60) were ‎significantly lower (P<0.001) compared to day 0. These results indicate that the modified ‎toggle splint with nylon suture is a promising treatment option for canine coxofemoral ‎luxation.